2014
DOI: 10.1002/anie.201410419
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of (±)‐Hippolachnin A

Abstract: The first total synthesis of the marine polyketide (±)-hippolachnin A has been achieved in nine linear steps and an overall yield of 9%. Rapid access to the oxacyclobutapentalene core structure was secured by strategic application of an ene cyclization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(46 citation statements)
references
References 59 publications
0
43
0
1
Order By: Relevance
“…341 They found that use of Mn(dpm) 3 (75% yield), Co(acac) 2 (63% yield) and Fe(acac) 3 (46% yield) all provided the undesired isomer 365 in >99:1 diastereoselectivity. Density function theory calculations at the B3LYP/6–311 + G(d,p) level of theory indicated that isomer 365 is more stable than the alternative epimer by ΔΔGº=1.0 kcal mol −1 .…”
Section: Hydrogenation and Isomerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…341 They found that use of Mn(dpm) 3 (75% yield), Co(acac) 2 (63% yield) and Fe(acac) 3 (46% yield) all provided the undesired isomer 365 in >99:1 diastereoselectivity. Density function theory calculations at the B3LYP/6–311 + G(d,p) level of theory indicated that isomer 365 is more stable than the alternative epimer by ΔΔGº=1.0 kcal mol −1 .…”
Section: Hydrogenation and Isomerizationmentioning
confidence: 99%
“…In 2015, Carreira and coworkers completed a total synthesis of (±)-hippolachnin A ( 245 ) (Figure 120) 341 During this endeavor, the team explored several strategies to set the desired cis-ethyl stereochemistry. One of these involved applying Baran’s conjugate addition reaction.…”
Section: C-c Bondsmentioning
confidence: 99%
“…The selected examples shown in Scheme 12 are representative. 131133 Although the yields are sometimes modest and stoichiometric iron is often required at the present stage of development, none of the transformations are straightforward to accomplish otherwise.…”
Section: Radical Approaches and Tasks Beyond Reach Of The Noble Cousinsmentioning
confidence: 99%
“…When asolution of 9 in MeCN/H 2 O was exposed to ceric ammonium nitrate in the absence of light with strict control of the reaction time and workup conditions, quinone 10 was obtained as the sole product in 76 %yield. [13] This product is likely formed by migration of the C(9)-C (14) bond, suggesting that the underlying mechanism for the ring expansion resembles that of aretroaldol-aldol sequence,similar to the DeMayo fragmentation, rather than aconcerted 1,2-shift (Scheme 3). Upon irradiation of ab enzene solution of 10 with blue LEDs,c lean formation of cyclobutane 11 was observed as as ingle diastereomer in 76 %y ield.…”
mentioning
confidence: 99%
“…[11] With 10 in hand, the feasibility of the key [2+ +2] photocycloaddition, aimed at assembling the core,c ould be investigated. [14,15] Thet ertiary alcohol in 16 was subsequently transformed to its O-thiocarbonate derivative and subjected to radical deoxygenation to generate 17 in 85 % yield over the two steps.Having the central cyclopentane core structure assembled in 17,w es ought to attach as uitable C 2 fragment to its methyl ketone moiety to close left hand side carbocycle of epicolactone.U nfortunately,t he selective addition of nucleophiles to the methyl ketone in 17 failed. This intramolecular photocycloaddition between aquinone and the internal C À C double bond of an electron deficient diene produced all three quaternary centers of epicolactone in as ingle step.…”
mentioning
confidence: 99%